Correlations between COPD Assessment Test and Modified British Medical Research Council Scoring and Degree of Airflow Limitation - Nuryanda, Dian; Suryadinata, Hendarsyah; Purba, Ambrosius (Althea Medical Journal, 2017)
Background: Chronic Obstructive Pulmonary Disease (COPD) Assessment Test (CAT) and Modified British Medical Research Council (MMRC) dyspnea scale are tools used to assess health status in COPD patients, while Forced Expiratory Volume in one second (FEV1) may represent the degree of airflow limitation. Assessment of COPD patients is rarely performed comprehensively. This study aimed to determine the relationships of CAT and MMRC dyspnea scale and the degree of airflow limitation in COPD patients. Methods: The study was conducted from September until October 2014 after obtaining approval from the Hasan Sadikin General Hospital Ethics Committee. This observational analytic study was performed on 77 medical records of COPD patients at Hasan Sadikin General Hospital. Patientsâ medical records included in this study were those with spirometry measurements results, CAT and MMRC dyspnea scale scoring. Data normality was analyzed using Kolmogorov-Smirnov Test. Pearsonâs Correlation was used for parametric variables. Spearmanâs correlation was used for non-parametric variables.Results: Results showed Pearsonâs correlation of CAT and FEV1 (p value=0.035 and r=0.240), and Spearmanâs correlation of MMRC dyspnea scale and FEV1 (p value=0.198 and r=0.148).Conclusions: CAT scoring is significantly correlated with the degree of airway limitation. MMRC dyspnea scale is not significantly correlated with the degree of airway limitation.